Exploring Pre-Service Teachers' Conceptual Understanding and Confidence in Geometrical Optics: A Focus on Gender and Prior Course Achievement - Derya Kaltakci-Gurel (MDPI AG, 2023)
This study investigated pre-service science teachers' conceptual understanding and confidence in geometrical optics with respect to gender and their previous achievement in geometrical optics course. A total of 189 (60% female and 40% male) pre-service science teachers who had completed geometrical optics course in state universities in Turkey participated in this study. The conceptual test instrument consisted of 20 items taken from the first tier of the Four-Tier Geometrical Optics Test (FTGOT) developed by the researcher, followed by a self-reported measure of teachers' confidence in the accuracy of their responses. The interest and experience scores were obtained through scales previously developed by the researcher, and these two variables were used as covariates in the analysis. The two-way between-groups ANCOVA tests were conducted to answer the research questions. The results showed that male pre-service teachers tend to have slightly higher conceptual understanding and confidence scores in geometrical optics than females with medium effect sizes while controlling for geometrical optics experience and interest scores. The findings were discussed, and implications for research in geometrical optics were provided.